Association of Gender-Affirming Hormone Therapy With Depression, Thoughts of Suicide, and Attempted Suicide Among Transgender and Nonbinary Youth - Green, Amy E.; DeChants, Jonah P.; Price, Myeshia N.; Davis, Carrie K. (Journal of adolescent health, 2022)
There are no large-scale studies examining mental health among transgender and nonbinary youth who receive gender-affirming hormone therapy (GAHT). The purpose of this study is to examine associations among access to GAHT with depression, thoughts of suicide, and attempted suicide among a large sample of transgender and nonbinary youth. Data were collected as part of a 2020 survey of 34,759 lesbian, gay, bisexual, transgender, queer, and questioning youth aged 13–24, including 11,914 transgender or nonbinary youth. Adjusted logistic regression assessed whether receipt of GAHT was associated with lower levels of depression, thoughts of suicide, and attempted suicide among those who wanted to receive GAHT. Half of transgender and nonbinary youth said they were not using GAHT but would like to, 36% were not interested in receiving GAHT, and 14% were receiving GAHT. Parent support for their child's gender identity had a strong relationship with receipt of GAHT, with nearly 80% of those who received GAHT reporting they had at least one parent who supported their gender identity. Use of GAHT was associated with lower odds of recent depression (adjusted odds ratio [aOR] = .73, p < .001) and seriously considering suicide (aOR = .74, p < .001) compared to those who wanted GAHT but did not receive it. For youth under age 18, GAHT was associated with lower odds of recent depression (aOR = .61, p < .01) and of a past-year suicide attempt (aOR = .62, p < .05). Findings support a relationship between access to GAHT and lower rates of depression and suicidality among transgender and nonbinary youth.